Using the sensomotor exercise system by speech therapists (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis examines the role and significance of the sensomotor exercise system in the training of future speech therapists. Sensomotor exercises are a crucial aspect of speech therapy, aimed at enhancing both the physical and cognitive development of individuals with speech and language impairments. These exercises improve motor coordination, stimulate neurological development, and contribute to the overall progress of speech skills. The study explores how integrating sensomotor exercises in speech therapy sessions helps in the rehabilitation of children with speech delays and disabilities. It also discusses how future speech therapists can effectively utilize these exercises to promote better communication abilities in their patients.